2013
DOI: 10.1016/j.jfma.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol from seeds of Cucurbita pepo against diabetes: Validation by in vivo experiments supported by computational docking

Abstract: The results provide pharmacological evidence of CPSE as an antihyperglycemic mediated by the interaction of various botanicals with multiple targets operating in diabetes mellitus (DM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 55 publications
0
30
0
1
Order By: Relevance
“…In addition, in silico constrained an noconstrained docking studies was performed using FRED and HYBRID programs to understand the mechanism of action with respect to three hypoglycemic proteins, PTP1 B, PPAR-γ, and DPP-IV with respect to 10 botanicals. In nonconstraint docking, all the tocopherols showed interaction in the active sites of the proteins [35]. A significantly reduction in oxidative markers and enhanced cecal and pancreatic characteristics were also observed.…”
Section: Anti-hyperglycemicmentioning
confidence: 90%
“…In addition, in silico constrained an noconstrained docking studies was performed using FRED and HYBRID programs to understand the mechanism of action with respect to three hypoglycemic proteins, PTP1 B, PPAR-γ, and DPP-IV with respect to 10 botanicals. In nonconstraint docking, all the tocopherols showed interaction in the active sites of the proteins [35]. A significantly reduction in oxidative markers and enhanced cecal and pancreatic characteristics were also observed.…”
Section: Anti-hyperglycemicmentioning
confidence: 90%
“…Furthermore, the tocotrienol-rich fraction of palm oil improved body glucose utilization and insulin sensitivity of diabetic mice, which was explained by the selective regulation of PPAR target genes. A recent study [143] with poloxamer-407 (PX-407)-induced type 2 diabetic Wistar rats, at which hyperglycemia response was induced due to loss of β-cell sensitivity to glucose, suggested the tocopherol-mediated antihyperglycemic effect of Cucurbita pepo seed oil. Observational studies have suggested the protective effect of alpha-tocopherol against the development of diabetes in humans subjects [144], although no additional benefits have been found with tocopherol supplementation [174].…”
Section: Tocopherols and Tocotrienols In Health Promotionmentioning
confidence: 99%
“…Activity of ESD2 fraction against DPP-IV inhibition suggests a close relationship with the highest tocopherol content in the fraction. Tocopherol isomers isolated from pumpkin seeds have shown a considerable interaction potential with DPP-IV and other proteins known to have diabetic therapeutic potential in HYBRID and FRED docking (Bharti et al, 2013). We assume that the efficacy of ESD2 fraction could be related to the highest α-tocopherol content compared to other fractions (Table 2).…”
Section: Antidiabetic Effectsmentioning
confidence: 99%